(untitled) (KULT_online, 2009)
Barbara Piatti’s dissertation on the Geography of Literature explicates the forms and semantics of literary and real-world spaces as well as their relation to each other. Using an approach that is part literary criticism, part cartography, the author develops a method of analysing places and spaces in literary texts and relating them to real-world topography. The Swiss region between Lake Lucerne and Mount Gotthard is her landscape of choice for a spatially organised history of literature.